2023
DOI: 10.9734/ajaar/2023/v21i2414
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation Strategies for Agro-pastoralists in Tanzania

Abstract: Climate change is seriously impacting the well-being of rural agro-pastoralists whose main livelihoods depend on rainfed agriculture. This study examined the factors that influence farmers' decisions to climate change adaptation measures. The study sampled 411 agro-pastoralist farmers and used factor analysis to extract correlated and uncorrelated adjustment strategies. These strategies include; Crop diversification, livestock diversification, small scale irrigation, rain-water harvesting and off-farm activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As a result, agro-pastoralists in the semi-arid regions of northern and central Tanzania remain highly vulnerable to the impacts of climate change. In addition, an assessment of diversification portfolios has shown that farmers can mitigate climate change risks by diversifying their crop and livestock enterprises as part of their adaptation strategies Sewando, [12], Nicol et al, [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, agro-pastoralists in the semi-arid regions of northern and central Tanzania remain highly vulnerable to the impacts of climate change. In addition, an assessment of diversification portfolios has shown that farmers can mitigate climate change risks by diversifying their crop and livestock enterprises as part of their adaptation strategies Sewando, [12], Nicol et al, [13].…”
Section: Introductionmentioning
confidence: 99%